IMPLEMENTASI METODE ACTIVE LEARNING DALAM MENINGKATKAN KECERDASAN KINESTETIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM: STUDI NATURALISTIK DI SMK KARYA GUNA I BEKASI - Sari, Rahma; Asiah, Siti (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2015)
The purpose of this study was to determine the extent of the implementation of active learning methods to improve kinesthetic intelligence and know the factors supporting and hindering the implementation of active learning methods. Results of this research is learning to use the Active Learning methods applied by teachers of Islamic education to make the learning process more actively marked by the enthusiasm of the students during the learning is very good. Inhibiting factors consist of internal factors and external factors. Internal factors it is difficult to get along because when students have a sense of shame and inferiority towards other friends on the shortcomings and the fear of being ridiculed by friends. As well as external factors are parenting parents to their children, parents can make a curb child can not develop their talents and abilities he has